Assessing moral values for higher civil service selections in India - Pandey, Manoj (2000)
Concerned about pervading degradation in moral values among members of higher civil service (who apparently serve as role models for their juniors) in India (as pointed out by Fifth Central Pay Commission, Shah Commission, etc.), the author analyses existing moral standards of these. He then takes a critical look at the efficacy of existing preventive and corrective measures in this regard. Advocating strict measures at the entry level itself to ensure that no individual with sub-standard morality gains entry, he presents a theoretical construct which perhaps could be tried as a remedy. - Reproduced
Keywords: Morale values - India; Civil service